Glyphosate on digestive enzymes activity in piava (Leporinus obtusidens) - Joseânia Salbego (Ciência Rural, 2014)
The effects of glyphosate, a nonselective herbicide (1.0 or 5.0mg L-1) on digestive enzymes activity (stomach and intestine) were evaluated in juveniles of piava (Leporinus obtusidens) after 90 days of exposure. The activity of acid protease, trypsin, chymotrypsin and amylase increased with the increase of glyphosate concentration. These results indicate that glyphosate affects digestive enzyme activities in this species, and may be an indicator of poor nutrient availability when fi sh survive in herbicide-contaminated water.